A Comparative Study of Esoteric Interpretation Between Ahlussunnah and Shi’a - Ahmad Zulki; Basnang Said (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2024)
The comparative study of esoteric interpretation (tafsir isyari) between Ahlussunnah and Shi’a reveals significant differences, both in substance and methodology. Despite these contrasts, a common ground between the two is the shared belief that esoteric interpretation is possible. However, this method can only be undertaken by those who are truly purified from sin and capable of profound contemplation, allowing them to perceive nothing but God in all aspects of life. Furthermore, any interpretation derived through this approach must ultimately be aligned with the textual sources of the Qur’an and Hadith. This study employs thematic, historical-critical, and comparative methods, while adopting a qualitative approach to analyze and compare the perspectives of Ahlussunnah and Shi’a on esoteric interpretation.